Examining associations among physical activity, motivation, attitudes, physical activity behaviour, and perceived fitness - Hakim, Luqmanul; Utomo, Gatot Margisal; Suganda, Mikkey Anggara; Ramos-Álvarezoliver , Oliver (UIR Press Bekerjasama dengan International Association of Physical Education and Sports, 2026)
Background: Elementary students’ perceived fitness is an important marker of health, yet few studies have examined how school-based physical activity programmes are associated with perceived fitness through motivation, attitudes toward physical activity, and physical activity behaviour. Objectives: This study aimed to examine the structural relationships among school-based physical activity programmes, motivation, attitudes toward physical activity, physical activity behaviour, and perceived fitness, and to test whether motivation, attitudes, and physical activity behaviour statistically mediated these relationships. Methods: A cross-sectional design was employed involving 150 Grade IV-VI students from public primary schools in Indonesia selected via cluster sampling. Variables were measured using five-point Likert-scale self-report instruments. School-based physical activity referred to students’ perceived engagement in existing programmes rather than exposure to an experimental intervention. Data were analysed using PLS-SEM. Results: School-based physical activity programmes were positively associated with students’ motivation (β = 0.575) and attitudes (β = 0.482). Motivation (β = 0.400) and attitudes (β = 0.336) were associated with more frequent physical activity behaviour, which showed a strong association with perceived fitness (β = 0.600). The model explained variance in physical activity behaviour (R² = 0.344) and perceived fitness (R² = 0.360). Conclusion: Physical activity programmes, motivation, attitudes, behaviour, and perceived fitness were interrelated among elementary school students, with physical activity behaviour acting as a key link between psychological factors and perceived fitness. These findings should be interpreted in light of the study’s cross-sectional design, reliance on self-report measures, and school sample, which limit causal inference and generalisability.